Media Narratives and Social Exclusion: A Structuration Analysis of Rohingya Refugee Coverage in Indonesia - Krida, Graha Wira; Rusadi, Udi (Sinergi International Journal of Communication Sciences, 2025)
This study examines the role of the media in shaping public meaning towards Rohingya refugees in Indonesia through Anthony Giddens' structuration theory. The problem discussed is how the media constructs narratives that are in line with the political and economic interests of the elite, which directly shape the public's meaning towards refugees as a "threat" or "burden." The purpose of this study is to understand in depth how the media uses its reporting mechanisms to shape meaning, control discourse, and legitimize policies regarding Rohingya refugees within the framework of the political economy communication structure. The theories and concepts applied include Giddens' structuration theory, which emphasizes three key elements: significance, dominance, and legitimacy, which provide a framework for empowering how the media shapes perceptions and policies on refugee issues. The methodology used is an analysis of news coverage about Rohingya refugees on SCTV media as an example of media in Indonesia, identifying narratives and interests conveyed in reporting. The analysis shows that coverage such as that carried out by SCTV, shapes public meaning through repeated narratives that depict refugees positively and negatively. The conclusion highlights the media structuring that determines the meaning of public opinion towards Rohingya refugees.